Genetic dilemma: eNOS gene intron 4a/b VNTR polymorphism in sepsis and its clinical features in Turkish children - Celik, Umit; Yildizdaş, Dinçer; Alhan, Emre; Celik, Tamer; Attila, Gülen; Sertdemir, Yaşar; Tepe, Tugay (The Turkish Journal of Pediatrics, 2008)
The role of endothelial nitric oxide synthase gene intron 4 a/b (eNOS4a/b) variable number of tandem repeats (VNTR) polymorphism in various diseases was investigated. We investigated whether this polymorphism is associated with susceptibility to sepsis and its clinical features such as acute respiratory distress syndrome (ARDS), multiorgan dysfunction syndrome (MODS) and shock. eNOS4a/b VNTR polymorphism was determined by the polymerase chain reaction in 100 children with sepsis and in 134 healthy controls. The genotype distribution of eNOS4 was not different between the patients and controls (p=0.44). There was no statistically significant association between genotypes/allele frequency and outcomes like mortality, MODS, ARDS, and shock (p>0.05). This is the first study that evaluates the effect of eNOS4a/b polymorphism in sepsis. We were unable to show a relationship between eNOS gene intron 4 a/b VNTR polymorphism and MODS, ARDS, mortality and shock. Larger studies that do research on the interaction of such genes are needed to clarify the association between eNOS4a/b polymorphism and sepsis.